ANALISIS KESALAHAN MAHASISWA TINGKAT AWAL DALAM MENYELESAIKAN SOAL ALJABAR - Ciptianingsari Ayu Vitantri (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
Describing the mistakes of early-level students in solving algebra problems and their causes is the purpose of this study. The algebra problem given is a SPLDV problem with one solution, many solutions and no solution. Descriptive qualitative is a type of this research, with the subject of early-level students taking linear algebra courses. Test and interview techniques were used in collecting data in this study. Then the data analyzed using analytical techniques consisting of data reduction, data display and conclusion drawing.The results showed that the errors of students in solving SPLDV questions with one solution were only in writing mathematical symbols for the final answer. Meanwhile, errors in solving SPLDV with many solutions, namely: (1) writing the final answer, (2) performing subtraction and division operations that involve algebra, (3) interpreting the calculation results into the answer. Meanwhile, errors in solving SPLDV with no solution, namely: (1) performing subtraction operations involving algebra, (2) interpreting the results of calculations into answers. The cause of the error is that students (1) do not understand what is meant by the SPLDV solution, (2) still fixated on previous knowledge, namely the solution to SPLDV is only one, (3) still fixated that the easiest way to solve SPLDV is by elimination, (4) not familiar with SPLDV with many solutions and no solutions.